Examining variation in interstage mortality rates across the National Pediatric Cardiology Quality Improvement Collaborative: do lower-mortality centres have lower-risk patients?. (21st June 2018) - Bates, Katherine E.; Yu, Sunkyung; Lowery, Ray; Pasquali, Sara K.; Brown, David W.; Manning, Peter B.; Uzark, Karen
Abstract: Background: Although interstage mortality for infants with hypoplastic left heart syndrome has declined within the National Pediatric Cardiology Quality Improvement Collaborative, variation across centres persists. It remains unclear whether centres with lower interstage mortality have lower-risk patients or whether differences in care may explain this variation. We examined previously established risk factors across National Pediatric Cardiology Quality Improvement Collaborative centres with lower and higher interstage mortality rates. Methods: Lower-mortality centres were defined as those with >25 consecutive interstage survivors. Higher-mortality centres were defined as those with cumulative interstage mortality rates >10%, which is a collaborative historic baseline rate. Baseline risk factors and perioperative characteristics were compared. Results: Seven lower-mortality centres were identified (n=331 patients) and had an interstage mortality rate of 2.7%, as compared with 13.3% in the four higher-mortality centres (n=173 patients, p<0.0001). Of all baseline risk factors examined, the only factor that differed between the lower- and higher-mortality centres was postnatal diagnosis (18.4 versus 31.8%, p=0.001). In multivariable analysis, there remained a significant mortality difference between the two groups of centres after adjusting for this variable: adjusted mortality rate was 2.8% in lower-mortality centres compared with 12.6% in higher-mortality centres, p=0.003. Secondary analyses identified multiple differences between groups in perioperative practices and other variables. Conclusions: Variation in interstage mortality rates between these two groups of centres does not appear to be explained by differences in baseline risk factors. Further study is necessary to evaluate variation in care practices to identify targets for improvement efforts.